The Integrity Crisis of State Apparatus: A Criminal Law Study of Systemic Corruption Practices - Gussman, Angga Aldilla (PT. Anagata Sembagi Education, 2026)
Corruption, as an extraordinary crime, has developed into a systemic practice that threatens the integrity of state officials and weakens governance. The main problem in eradicating corruption lies not only in law enforcement but also in normative weaknesses, particularly the vagueness of norms regarding the element of